Services and Handling of Maternal Emergencies in Hospitals Based on Law - Naurah, Gladdays; Fatimah, Fitri; Simarmata, Marice; Sidi Jambak, Redyanto (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
This research aims to research Services and Handling of Maternal Emergencies in Hospitals Based on Law.This research is qualitative research with a descriptive analytical approach. The data required in the research was collected through in-depth interviews with informants/subjects whose criteria had been selected using purposive sampling by the researcher. The conclusion of this material highlights the importance of understanding the legal basis that regulates maternal emergency services and management in hospitals, both from the perspective of the responsibilities of health institutions and the rights and protection of patients. With the Minister of Health Regulation Number 21 of 2021 concerning the implementation of health services during pre-pregnancy, pregnancy, childbirth and the post-natal period, contraceptive services and sexual health services. Article 16 paragraph (1) which reads "delivery is carried out in a health service facility", it is hoped that the birth that is carried out must be handled directly by a medical team and in a health facility to reduce maternal and infant mortality. However, from the data obtained there are still several villages where births take place in non-health facilities, so that with births still taking place in non-health facilities, the implementation of Minister of Health Regulation Number 21 of 2021 is still not optimal. By complying with applicable regulations and following best practices in Maternal health services are expected to improve the safety and welfare of pregnant women and unborn babies.